Modelling reaction and diffusion in a wax-filled hollow cylindrical pellet of Fischer Tropsch catalyst. (2nd November 2019) - Hubble, R.; York, A.P.E.; Dennis, J.S.
Highlights: A 2-D model was investigated for the FT reaction for solid and hollow cylindrical Co catalyst pellets. Conditions considered where liquid hydrocarbons accumulate in the pores. Effectiveness factor exceeded that of spherical and slab geometry for Thiele moduli range 0.75–1.15. FT growth parameter, α, in this range was lowest with cylinders and so gave greatest CH4 selectivity. Abstract: Previous modelling of fixed-bed, Fischer-Tropsch (FT) reactors has demonstrated the advantages relative to spherical pellets of using cylindrical and shaped pellets to provide improved transport attributes under conditions relevant to industrial operation. However, mass transport models have focussed on the investigation of transport within pellets with spherical symmetry, whilst detailed investigations of more complex shapes have not been undertaken. Here, a pseudo-isothermal, steady-state, two-dimensional model was investigated for catalyst pellets of cylindrical form, both solid and hollow. A cobalt-based catalyst was considered at conditions where the rate of condensable hydrocarbon generation is large enough to result in the accumulation of liquid hydrocarbons in the pores of a catalyst. It was found that effectiveness factors were bounded by those of sphere and slab above and below Thiele moduli of ∼0.75 and ∼1.15, respectively, for the conditions examined, with the effectiveness factors exceeding those of both sphere and slab models between these moduli. Here, comparisons were made on the basis of the characteristic diffusion length, the catalyst particle's volume divided by its external surface area. However, values of the FT chain growth parameter, α, between these values of Thiele modulus were lower than those of both sphere and slab geometry, and thus under these conditions hollow cylinders gave the greatest methane selectivity.